Micro-Scale Heat Transfer Characteristics of Evaporating Meniscus for Alkali Metals in High-Temperature Heat Pipes - MA Shasha, DING Shengjie, LIU Limin, ZHAO Changying, GU Hanyang, GONG Shuai (Shanghai Jiaotong Daxue xuebao)
To elucidate the micro-scale heat transfer mechanisms during the liquid-vapor phase change process in the wick of the high-temperature alkali metal heat pipes, this paper investigates the micro-scale heat transfer characteristics in the evaporating meniscus region for different alkali metals including potassium, sodium, and lithium by using the contact line heat transfer model. The distributions of liquid film thickness, contact angle, interface temperature, and heat flux at the evaporating meniscus region for different alkali metals are obtained under the same saturation vapor pressure and wall superheat. The results show that due to the high thermal conductivity of alkali metals, the contact line heat transfer characteristics of potassium, sodium, and lithium are significantly different from those of water. For alkali metals, the heat transfer in the micro region near the three-phase contact line is dominated by the thermal resistance at the vapor-liquid interface. Among these alkali metals, lithium has the highest micro-scale heat transfer performances. The thickness of the non-evaporating liquid film, the apparent contact angle and the pressure gradient of the liquid film are self-tuned according to the wall superheat, and a higher superheat results in a thinner non-evaporating liquid film, a larger apparent contact angle, and a larger pressure gradient. The adsorbed film region, where the non-evaporating liquid film is adsorbed on the wall, is dominated by the disjoining pressure. In the thin-film region, both disjoining pressure and capillary pressure contribute to the total pressure difference, which drives the liquid from the intrinsic meniscus region. The curvature of the vapor-liquid interface remains constant, and the capillary pressure dominates in the intrinsic meniscus region.